C5a-C5aR1 axis mediates lung inflammation and fibrosis induced by single-walled carbon nanotubes via promoting neutrophils recruitment - Jiaojiao Zhu; Xiang Zhang; Lanlan Li; Hongxu Yang; Hang Liu; Danyang Wu; Zikai Liu; Bin Liu; Tong Shen (Ecotoxicology and Environmental Safety)
A mounting number of studies have been documenting strong pro-inflammatory and pro-fibrotic effects of carbon nanotube (CNT). However, the molecular mechanisms of single-walled CNT (SWCNT)-provoked lung injury remain to be elucidated. Here, we established a mice model of SWCNT-induced lung injury by intratracheal instillation and found that C5a-C5a receptor-1 (C5aR1) signaling was significantly activated along with abundant neutrophils recruitment in lungs at early phase post SWCNT administration, which were positively correlated with early lung inflammation and late pulmonary fibrosis. C5a-C5aR1 signaling activation and neutrophils recruitment were subsequently decreased in a time-dependent manner. Furthermore, inhibition of C5a-C5aR1 axis with C5aR1 antagonist PMX205 treatment not only dramatically reduced neutrophils recruitment and inflammatory cytokines secretion at early phase, but also effectively alleviated early lung inflammation and late pulmonary fibrosis induced by SWCNT exposure. In conclusion, our study provides novel insights into the underlying biological mechanism that C5a-C5aR1 axis regulates neutrophils recruitment-mediated lung injury induced by SWCNT, may help to develop therapeutic strategies for SWCNT-provoked lung injury.